The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1111/j.1365-2648.2011.05764.x
|View full text |Cite
|
Sign up to set email alerts
|

Involving practice nurses in primary care research: the experience of multiple and competing demands

Abstract: The nurses were key to the delivery of the trial. If practice nurses are to develop a research role in their professional work, it is important to understand their perceptions and the impact such involvement has on them and their practice. Consideration of these factors is consequently valuable when developing research in primary care settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(59 citation statements)
references
References 30 publications
(28 reference statements)
2
57
0
Order By: Relevance
“…Although the research output of some APs was considerable, most found it hard to find the time to conduct research, a common finding in other studies also, 54 and had to spend personal time on their research activities. These individuals were high achievers and demonstrated strong personal initiative 55 that drove them to succeed.…”
Section: Discussionmentioning
confidence: 96%
“…Although the research output of some APs was considerable, most found it hard to find the time to conduct research, a common finding in other studies also, 54 and had to spend personal time on their research activities. These individuals were high achievers and demonstrated strong personal initiative 55 that drove them to succeed.…”
Section: Discussionmentioning
confidence: 96%
“…Across different countries, research results have revealed a very restricted level of evidence-based practice (EBP) use among nurses (Brown et al 2010, Mashiach Eizenberg 2011, Boase et al 2012, Bostr€ om et al 2013, Stokke et al 2014, Skela-Savi c et al 2016. The reasons behind the limited extent of EBP use include perceived lack of time for reading literature, inadequate institutional support for implementing new practices, lack of knowledge, experience, resources and supportive leadership and insufficient authority for implementing change into practice (Meijers et al 2006, Brown et al 2010, Kajermo et al 2010, Breimaier et al 2011, Moreno-Casbas et al 2011, Solomons & Spross 2011, Akerjordet et al 2012, Hewitt-Taylor et al 2012, Timmins et al 2012, Friesen-Storms et al 2014, Murphy 2014, Stokke et al 2014, Yoder et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of time in PNs' adherence to case management elements has been identified before [20,21] .…”
Section: Discussionmentioning
confidence: 99%